Hybrid Identity Development in the Biggest Cities of Lithuania: The Case of Russian Youth - Kubiliūtė, Skirmantė (Taikomoji kalbotyra, 2021)
This article aims to investigate the development of ethnic identity. The main focus of the study is the young generation of Russian minority living in Lithuania’s biggest cities – Vilnius, Kaunas and Klaipėda. The hypothesis of this study is based on previous research and tends to examine whether the younger generation of Russians have difficulties identifying themselves as members of a specific ethnic group and/or have hybrid ethnic identity. In order to collect the necessary data, qualitative and quantitative methods were used. The main age group of this study was youngsters aged from were 15 to 29 y.o. There were also a control group of older Russians aged from 45 to 60 y.o. The latter group was selected in order to compare the data. The study has shown that around 20 percent of all young participants have double or hybrid ethnic identity. The majority of them identified with two ethnic groups and described themselves as Russian-Lithuanians. Almost half of the young participants had certain doubts in categorizing themselves as members of a particular ethnic group. Even more, around a tenth of all the participants avoided assigning themselves to any ethnic group and defined themselves as “humans”, “Europeans” or “world citizens”. Certain differences between the three cities have been observed as well. Both older and younger Russians from Klaipėda and Vilnius have stronger bonds with their ethnic group and language comparing to Russians from Kaunas. Therefore, the processes of assimilation in this city are more prominent that hybridization. This study has revealed not only the latest tendencies of identity development within Russian minority group, but also numerous different factors that might influence these trends. Complex processes of self-identification as well as the formation of hybrid ethnic identity in young individuals might be caused by globalization, active migration of people, rapid spread of information, multilingualism.